The big book of Beatrix Potter - Potter, Beatrix, 1866-1943. (New York : Portland House, 1997)
Nineteen classic tales by Beatrix Potter about Peter Rabbit and his many friends and relatives.
The tale of Peter Rabbit -- The tailor of Gloucester -- The tale of Squirrel Nutkin -- The tale of Benjamin Bunny -- The tale of two bad mice -- The tale of Mrs. Tiggy-Winkle -- The pie and the patty-pan -- The tale of Mr. Jeremy Fisher -- The story of a fierce bad rabbit -- The story of Miss Moppet -- The tale of Tom Kitten -- The tale of Jemima Puddle-duck -- The roly-poly pudding -- The tale of the Flopsy bunnies -- The tale of Mrs. Tittlemouse -- The tale of Timmy Tiptoes -- The tale of Mr. Tod -- The tale of Pigling Bland -- The tale of Johnny Town-mouse.
Keywords: Children's stories, English; Animals -- Juvenile fiction; Animals -- Fiction; Short stories; Animals; Children's stories, English; Fiction; Juvenile works; Fiction